Effects of student-centered learning and formative assessment on first year students of a non-government college in Bangladesh - Md. Anisur Rahman (CV. FOUNDAE, 2023)
Background: In the evolving landscape of education, student-centered learning approaches and formative assessments have gained prominence as key to enhancing the quality of higher education. This is particularly pertinent in Bangladesh, where traditional teaching methods are still prevalent, underscoring the significance of these strategies.Aim: This research aims to explore the impact of implementing student-centered learning and formative assessment on first-year university students at a non-governmental university in Bangladesh, highlighting how these methods influence the learning process.Method: Employing a qualitative approach, data was gathered through surveys conducted among fifteen first-year political science students at a non-governmental higher education institution in Bangladesh.Results: The study revealed increased student engagement in understanding material and improved academic performance in classes that adopted student-centered approaches and formative assessments.Conclusion: This research confirms that student-centered learning combined with formative assessment contributes positively to enhancing the quality of learning at the higher education level. It underscores the need for pedagogical improvements in Bangladesh to encourage broader implementation of these methods, which in turn could enrich the learning process and educational outcomes for students.